Pom34 mRNA is the Only Target of the Sesa Network - Ergüden, Bengü (My University, 2017)
MPS2 is an essential gene required for the insertion of Saccharomyces cerevisiae centrosome into the nuclear membrane. Upon its deletion, cell cycle is stopped and the cell dies. Recently, we reported that SESA network can suppress essential role of MPS2. Detailed analysis showed that SESA is a system which suppresses centrosome duplication defects by inhibiting the translation of a subset of mRNAs selectively. In this study, we report the results of a genome-wide deletion screen which unearthed Pom34 mRNA as the only target of the SESA network.
Keywords: Biyoloji; Genetik ve Kalıtım; Hücre Biyolojisi